Interprofessional Working in Practice – Avoiding a Theory-Practice Gap - Jackson, Ann; Bluteau, Patricia; Furlong, Janet (International Journal of Practice-based Learning in Health and Social Care, 2016)
This paper aims to encourage and promote further discussion around the theme of the theory and practice gap in the teaching and practice of interprofessional education (IPE) in pre-registration health and social care. Following a brief history of IPE, we consider the importance of providing students with supported opportunities to observe, learn and put into practice IPE. We also highlight the necessity of involving practitioners in creating health professionals who are ‘fit for purpose’ at qualification.